2017
DOI: 10.1002/path.4872
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear inclusion bodies of mutant and wild‐type p53 in cancer: a hallmark of p53 inactivation and proteostasis remodelling by p53 aggregation

Abstract: Although p53 protein aggregates have been observed in cancer cell lines and tumour tissue, their impact in cancer remains largely unknown. Here, we extensively screened for p53 aggregation phenotypes in tumour biopsies, and identified nuclear inclusion bodies (nIBs) of transcriptionally inactive mutant or wild-type p53 as the most frequent aggregation-like phenotype across six different cancer types. p53-positive nIBs co-stained with nuclear aggregation markers, and shared molecular hallmarks of nIBs commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 66 publications
(95 reference statements)
5
74
0
Order By: Relevance
“…HEK293 cells (female) stably expressing UbG76V-GFP (Dantuma et al, 2000; De Smet et al, 2017) were cultured in Dulbecco’s modified Eagle’s medium (DMEM; Biochrom) supplemented with 10 % (v/v) fetal bovine serum (Gibco), 2 mM L-glutamine (Gibco), penicillin-streptomycin (Thermo Fisher) and non-essential amino acids (Gibco). Transfection was carried out using FuGENE 6 (Promega).…”
Section: Star Methodsmentioning
confidence: 99%
“…HEK293 cells (female) stably expressing UbG76V-GFP (Dantuma et al, 2000; De Smet et al, 2017) were cultured in Dulbecco’s modified Eagle’s medium (DMEM; Biochrom) supplemented with 10 % (v/v) fetal bovine serum (Gibco), 2 mM L-glutamine (Gibco), penicillin-streptomycin (Thermo Fisher) and non-essential amino acids (Gibco). Transfection was carried out using FuGENE 6 (Promega).…”
Section: Star Methodsmentioning
confidence: 99%
“…HEK293 cells stably expressing Ub G76V ‐GFP (Dantuma et al , ; De Smet et al , ) were transfected with the indicated constructs for co‐culture assays or incubated with conditioned media from GA 175 ‐RFP‐ or RFP‐expressing cells for 48 h. Subsequently, receiver cells were harvested and analyzed by flow cytometry for GFP and RFP fluorescence using an Attune NxT Cytometric Analyser (Thermo Fisher) at the Imaging Facility of the Max Planck Institute of Biochemistry, Martinsried. Fluorescence was detected using the following settings: GFP Ex 488 nm, Em 530/30 nm, tagRFP Ex 561 nm, and Em 586/15 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Given that mutant p53 is inhibiting the function of TAp63 and TAp73, it has been postulated that through aggregation, mutant p53 might inactivate its family members, preventing them from interacting with their target gene promoters [51,66]. Aggregation was identified as punctate staining for p53 in the cytoplasm or nucleus [67]. A punctate p53 staining has been identified in cancers with mutant or wildtype p53 expression and has been correlated to worse outcomes [67].…”
Section: Mutant P53 Aggregation and Other Binding Partnersmentioning
confidence: 99%